2022
DOI: 10.1371/journal.pone.0269180
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for metabolic bone disease of prematurity: A meta-analysis

Abstract: Objective To investigate the risk factors for metabolic bone disease of prematurity (MBDP), and to provide a reference for the prevention of MBDP. Methods The databases including China Biomedical Literature Service System, China National Knowledge Infrastructure, Wanfang Data, and Weipu Periodical Database, PubMed, Web of Science, Embase, Cochrane Library and other databases were searched for studies on the risk factors for MBDP published up to June 18, 2021. RevMan 5.3 and Stata 14.1 software were used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
0
21
0
3
Order By: Relevance
“…In this study, multivariate logistic regression analysis showed that GA was a risk factor for MBD. Several studies have shown that the risk of developing MBD is increased for neonates born at a GA < 32 weeks, and in preterm infants, the younger the GA and the lower the birth weight, the higher the incidence and severity of MBD[6, 13,14]. The main reasons are related to the following factors: Mineralization begins during the embryonic period, but the accumulation of minerals mainly occurs in the third trimester of pregnancy, especially at 32-36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, multivariate logistic regression analysis showed that GA was a risk factor for MBD. Several studies have shown that the risk of developing MBD is increased for neonates born at a GA < 32 weeks, and in preterm infants, the younger the GA and the lower the birth weight, the higher the incidence and severity of MBD[6, 13,14]. The main reasons are related to the following factors: Mineralization begins during the embryonic period, but the accumulation of minerals mainly occurs in the third trimester of pregnancy, especially at 32-36 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that ELBW and VLBW had a significant influence on the risk of MBD during infancy. Previous studies 7,19,30,31 identified birth weight along with gestational age as the strongest risk factors for MBD in preterm infants and recommended that infants with birth weights less than 1500 g be screened for MBD. 32 Approximately 80% of fetal bone mineral accretion occurs during the last 3 months of pregnancy, and preterm neonates will miss, partially or fully, this critical period of bone growth.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%
“…To improve linear growth in preterm infants with risk factors for MBD, regular follow-up and monitoring are necessary. The objectives are to maintain blood calcium and blood phosphorus within normal limits and avoid excessive urinary calcium excretion [ 95 ].…”
Section: Screening and Monitoringmentioning
confidence: 99%
“…For early diagnosis of mineral deficiency, measurement of serum biochemical markers is essential. The most commonly used blood biochemical indicators are serum calcium, serum phosphorus, ALP, PTH, and 25(OH)D [ 95 ].…”
Section: Screening and Monitoringmentioning
confidence: 99%
See 1 more Smart Citation